Formation of the Poliovirus Replication Complex Requires Coupled Viral Translation, Vesicle Production, and Viral RNA Synthesis - Egger, Denise (American Society for Microbiology, 2000)
Poliovirus (PV) infection induces the rearrangement of intracellular membranes into characteristic vesicles which assemble into an RNA replication complex. To investigate this transformation, endoplasmic reticulum (ER) membranes in HeLa cells were modified by the expression of different cellular or viral membrane-binding proteins. The membrane-binding proteins induced two types of membrane alterations, i.e., extended membrane sheets and vesicles similar to those found during a PV infection. Cells expressing membrane-binding proteins were superinfected with PV and then analyzed for virus replication, location of membranes, viral protein, and RNA by immunofluorescence and fluorescent in situ hybridization. Cultures expressing cellular or viral membrane-binding proteins, but not those expressing soluble proteins, showed a markedly reduced ability to support PV replication as a consequence of the modification of ER membranes. The altered membranes, regardless of their morphology, were not used for the formation of viral replication complexes during a subsequent PV infection. Specifically, membrane sheets were not substrates for PV-induced vesicle formation, and, surprisingly, vesicles induced by and carrying one or all of the PV replication proteins did not contribute to replication complexes formed by the superinfecting PV. The formation of replication complexes required active viral RNA replication. The extensive alterations induced by membrane-binding proteins in the ER resulted in reduced viral protein synthesis, thus affecting the number of cells supporting PV multiplication. Our data suggest that a functional replication complex is formed in cis, in a coupled process involving viral translation, membrane modification and vesicle budding, and viral RNA synthesis.